INFLUENCE OF INCOME STREAMS ON MARKET RETURNS OF COMMERCIAL BANKS LISTED IN NAIROBI SECURITIES EXCHANGE - Kimwomi, Boniface Okeri; Muturi, Prof. Willy (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to determine the influence of income streams on market returns of Commercial Banks Listed in the Nairobi Securities Exchange. Methodology: The study used descriptive research design and conducted a Census Survey on all the 11 Commercial Banks listed in the NSE using Secondary data from Audited Financial Reports and NSE 20 Share Index for a period between 2012 and 2017 (both inclusive) that were collected from the Listed banks' individual, KNBS, CBK and NSE websites with the aid of the secondary data collection sheet. The data collected was analyzed using SPSS Version 22.0 and with its help Multi-regression analysis model was used to analyze the data and present the results on tables. Coefficient of determination (R2) and ANOVA were used to test the hypothesis while T-Test and F-Test were be used to establish the significance of the model at 95% confidence level. Findings: The correlation results revealed that all the predictors of Income Streams except Dividend Income had a significant influence on Market Returns (NSE 20 Share Index). On the other hand, the regression findings of the study were that there was a positive significant Influence of all Income Streams predictors combined on Market Returns of Commercial Banks listed in the NSE. The F-statics was also significant at 0.027 to explain the relationship. Unique contribution to theory, practice and policy: The study recommended that in order to improve the Market Returns, the management of Listed Commercial Banks need to identify and invest on Income Streams that yield high returns and they should embrace Income Streams Diversification. Keywords: Income streams, stock markets returns, commercial banks, Nairobi Securities Exchange